Standard-Dose Proton Pump Inhibitors in the Initial Non-eradication Treatment of Duodenal Ulcer: Systematic Review, Network Meta-Analysis, and Cost-Effectiveness Analysis - Zhang, Jiaxing; Ge, Long; Hill, Matt; Liang, Yi; Xie, Juan; Cui, Dejun; Li, Xiaosi; Zheng, Wenyi; He, Rui (Frontiers in Pharmacology, 2019)
Background: Short-term use of standard-dose proton pump inhibitors (PPIs) is the first-line initial non-eradication treatment for duodenal ulcer (DU), but the choice on individual PPI drug is still controversial. The purpose of this study is to compare the efficacy, safety, and cost-effectiveness of standard-dose PPI medications in the initial non-eradication treatment of DU. Methods: We searched PubMed, Embase, Cochrane Library, Clinicaltrials.gov, China National Knowledge Infrastructure, VIP database, and the Wanfang database from their earliest records to September 2017. Randomized controlled trials (RCTs) evaluating omeprazole (20mg/day), pantoprazole (40mg/day), lansoprazole (30mg/day), rabeprazole (20mg/day), ilaprazole (10mg/day), ranitidine (300mg/day), famotidine (40mg/day), or placebo for DU were included. The outcomes were 4-week ulcer healing rate (4-UHR) and the incidence of adverse events (AEs). A network meta-analysis (NMA) using a Bayesian random effects model was conducted, and a cost-effectiveness analysis using a decision tree was performed from the payer’s perspective over one year. Results: A total of 62 RCTs involving 10,339 participants (8 interventions) were included. The NMA showed that all the PPIs significantly increased the 4-UHR compared to H2 receptor antagonists (H2RA) and placebo, while there was no significant difference for 4-UHR among PPIs. As to the incidence of AEs, no significant difference was observed among PPIs, H2RA, and placebo during 4-week follow-up. Based on the costs of both PPIs and management of AEs in China, the incremental cost-effectiveness ratio per quality-adjusted life year (in US dollars) for pantoprazole, lansoprazole, rabeprazole, and ilaprazole compared to omeprazole corresponded to 5134.67, 17801.67, 25488.31, and 44572.22, respectively. Conclusions: Although the efficacy and tolerance of different PPIs are similar in the initial non-eradication treatment of DU, pantoprazole (40mg/day) seems to be the most cost-effective option in China.